False Polarization and False Moderation: Political Opponents Overestimate the Extremity of Each Other's Ideologies but Underestimate Each Other's Certainty. Issue 5 (July 2018) - Blatz, Craig W.; Mercier, Brett
Past research finds that people hold moderate views on political issues while believing others are extreme. This false polarization has been demonstrated across a variety of different attitude dimensions and is explained by naive realism, the belief that one holds an unbiased view of reality. We argue that because people believe they see the world objectively, they should be very certain about their opinions, more certain than others expect. In three studies, we tested this false moderation of attitude certainty hypothesis and attempted to replicate past research on false polarization of attitude stance and perceived ideology of others. All three studies revealed a false moderation effect on judgements of certainty. Additionally, we replicate the finding that people false polarize others' ideology but do not find evidence for false polarization of specific stance.